External excitation effects on the flutter characteristics of a 2-DOF rigid rectangular panel. Issue 209 (February 2021) - Yuan, Wenyong; Laima, Shujin; Chen, Wen-Li; Li, Hui
Abstract: The flutter of a rigid panel is considered as a super/subcritical Hopf bifurcation. However, the initial conditions of such characteristics have not been extensively explored. In this study, a 2-DOF rigid rectangular panel was tested in a wind tunnel at zero angle of attack to investigate the flutter stability, with and without external excitations, in the Reynolds number range of 6.15–8.21×10 4 . Coupled flutter occurs abruptly and evolves into four stages as the inflow wind velocity reaches a critical flutter velocity, U cr . A hysteresis loop is observed when the wind velocity is decreased from U cr to 0.75 U cr . External excitations are applied to the test model stepwise in the hysteresis region to examine the stability conditions. The critical excitation amplitude, A cr, is determined, which corresponded to the unstable limit cycle of the subcritical Hopf bifurcation. A fitted equation of the bifurcation is provided to correlate the flutter amplitude and the critical excitation amplitude with wind speed. PIV measurements show the flow field evolution around the panel during the entire flutter occurrence process. The size of the leading-edge vortex expands as the oscillation amplitude increases, then convects to the trailing edge and eventually sheds into the wake region. Wake patterns of each flutter stage were illustrated and analyzed using the Dynamic Mode Decomposition (DMD) method. Highlights: Four stages are found during the flutter occurrence of a rectangular panel. A subcritical Hopf bifurcation is determined by external excitations. The flow fields during flutter are shown using PIV measurement.